World Breastfeeding Week 2024: An Intimate Breastfeeding Education Session with Working Mothers in BASF Indonesia - Dewanti, Lintang; Monica, Risda; Suri, Anggun; Larasati, Dewi (Pengabdian Masyarakat Sumber Daya Unggul, 2024)
The theme for WBW 2024, "Closing the Gap: Breastfeeding Support for All," underscores the necessity of equitable breastfeeding support, especially for working mothers who face unique challenges. This paper discusses the implementation of an intimate breastfeeding education session held by IKMI in collaboration with PT. BASF Indonesia during WBW 2024. The session aimed to provide essential knowledge, practical advice, and emotional support to working mothers to promote breastfeeding within the workplace. The initiative involved a collaborative effort between IKMI, healthcare professionals, lactation counselors, and BASF Indonesia’s internal human resources team. The session included expert presentations and interactive workshops, employing methods such as demonstrations and the Socratic Method to engage participants. Eleven female staff members participated, receiving hands-on guidance on breastfeeding techniques and management. The session was structured to be interactive and supportive, featuring opening remarks, expert presentations on breastfeeding benefits and challenges, and interactive Q&A. Participants reported enhanced knowledge and confidence in breastfeeding practices, as well as a stronger sense of community and support among peers. The breastfeeding education session was a successful initiative that significantly contributed to promoting breastfeeding within the workplace. Recommendations include conducting regular education sessions, investing in better lactation facilities, implementing supportive workplace policies, and creating ongoing peer support networks.